Ownership Of Computer And Its Usage At Home: A Case In Malaysia. - Loke, Yiing Jia; Foo, Ching Szu (2008)
The multi-functionality of computer and the increased accessibility of Internet have created a demand for computers at home which previously was concentrated in offices. Using the Heckman two-step model and by combining socio-economic factors and insights from Becker's (1965) theory on allocation of time in the household with information system theories, it is found that i) the household allocation of resources, ii) age and gender and iii)household social environment are significant in determining computer purchase decision and its extent of usage in households. Responses collected from 500 computer users are used in the study.